(3MdjI GdeMGVQI aj UfGYI GdTYQ hGfhGYgs - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s ((3GHQGgje Hf eMeO GdZSGfi GdTgjQ HGdhRjQ s)
(3ChdgG (B:s
(3gPG HGH ai fXe GdefKhQ bGd CHh Ydi hef GdTYQGA GdeHJOYjf WGFag JNV hJdHg EYJeGOG Ydi efKhQ GdcdGe Ohf efXhQ s
(3BNQgG (B:s
(3cUQY GdRLGLI eGJSJWjY ca GdUfGY dg Cf JMjQG s
(3HgG fXGe GdJYbjHIs
(3YdjgG JMHjS Ydi LGeY GdbQhjjf ef GdbGFO CHj Ydi HNd GdQDSGA GdQDSjf SfI (B1118s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B82s
Keywords: (3GdCOHs